Are political parties able to influence public opinion in both leftist and rightist ideological directions? Results from a survey experiment with Danish social democratic voters - Jensen, Kristoffer Skovgaard (Politica, 2025)
Public opinion and the responsiveness of the elected political parties are essential for a modern democracy to function. But to what extent do political parties play a part in the formation of public opinion, and is the party influence independent of ideological direction? In this article, I argue that citizens use their partisanship as a social group identity, which enables them to adopt the party’s policy opinions. By examining a survey experiment conducted with more than 3000 Danish voters (771 social democratic voters), this article finds that social democratic voters express more conservative (liberal) opinions when they are exposed to conservative (liberal) party cues from the Social Democratic Party. By disentangling party and ideology, the research design in this article offers the opportunity to examine party influence on public opinion in both ideological directions in a realistic Danish context.